Penerapan Choreography Message Broker Untuk Transaksi Data Berbasis Asynchronous RESTful - Imanuel, Desendo; Rini, Maria Nila Anggia; Susanto, Budi (Jurnal Terapan Teknologi Informasi, 2024)
Currently, hospitals under the Christian Foundation for Public Health (Yayasan Kristen untuk Kesehatan Umum - YAKKUM) operate information systems independently. This implies that each hospital builds and manages its information system independently without systematic involvement with other hospitals. This triggers the emergence of heterogeneous data, necessitating data integration. In enterprise-scale applications, integration issues among application system components will increase with the growing needs and complexity of the application. One way to address this is by implementing middleware with a choreography approach as an intermediary between services. The system implements Axon Server as a message broker configured with an event handler in tracking processor mode. Each service has its own database supported by the implementation of infrastructure using Docker. The system is tested based on scenarios testing the reliability of data transactions between services in rollback or compensating transactions, choreography, and event consumption. Test results indicate that all testing scenarios were successfully executed even when services underwent a reboot during the testing process. Additionally, testing with unit tests, component tests, and integration tests successfully completed 46 test cases per 46 total test cases for the User Service and 27 test cases per 27 total test cases for the Auth Service. However, the test results also revealed anomalies or bugs when processing data transactions based on the saga pattern.